THE EFFECT OF FINANCIAL LITERACY ON FINANCIAL MANAGEMENT BEHAVIOR WITH FINANCIAL RISK ATTITUDE AND FINANCIAL TECHNOLOGY AS MEDIATING VARIABLES - Hamidah, Hamidah; Widyastuti , Umi; Siti Robihah Al Maliyah (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
This study aims to determine the extent to which financial literacy affects the financial management behavior of MSME actors in DKI Jakarta, by considering the role of attitudes towards financial risk and the use of financial technology as mediating variables. The background of this study comes from the fact that there are still many MSME players who are not able to manage their finances optimally, even though access to information and digital financial services is quite widespread. Using a quantitative approach, data were collected from 156 individual business owners and analyzed through the Partial Least Squares Structural Equation Modeling (PLS-SEM) method. The results showed that financial literacy did not have a significant direct effect on financial management behavior. However, financial literacy has a positive and significant effect on financial risk attitudes and financial technology. These two variables directly influence financial management behavior, and act as mediators in the relationship between financial literacy and financial management behavior. These findings emphasize the importance of a financial literacy approach that not only focuses on increasing knowledge, but also includes the formation of rational risk attitudes and the practical use of financial technology. This kind of literacy strategy is considered more relevant and effective in improving the financial management of MSME actors, especially in the current digital era.